Failure and life evaluation of EB-PVD thermal barrier coatings using temperature-process-dependent model parameters. (1st August 2019) - Zhang, B.C.; Chen, Kuiying; Baddour, N.; Patnaik, P.C.
Abstract: Using experimentally measured temperature-process-dependent model parameters, the failure analysis and life evaluation were conducted for electron beam-physical vapor deposition thermal barrier coatings (EB-PVD TBCs) with Pt-modified β-NiAl bond coats deposited on Ni-base single crystal superalloys. The failure analysis and life model were applied to two failure modes of A and B identified experimentally subjected to thermal cyclic process. The rumpling effect and the associated roughness of the constituent coating layers were shown to play a key role in evaluating the coating's failure and life. The experimentally determined temperature-dependent thickness of thermally grown oxide (TGO), interfacial roughness, elastic moduli of the constituent coatings and their coefficients of thermal expansion were incorporated into the life prediction model. The maximum average rumpling amplitude of the bond coat/TGO interface associated with bond coat rumpling was used in failure analysis and life evaluation for the failure mode A. The global wavelength related to the interface rumpling and its radius curvature were identified as essential parameters in life evaluation, and the predicted life results for failure mode A were verified by existing furnace cyclic test data. For the failure mode B, the crack growth rate along the TGO/top coat interface was calculated using the crack length dependent fracture toughness.